Frequency and relationship of sleep deprivation and disability in chronic neck pain - Mirza Baig, Aftab Ahmed; Khan, Farhan Ishaque; Abid, Hafza Zobia; Waheed, Syeda Sana; Hassan, Rabia; Shehzadi, Hafsa (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the frequency and relationship of disability and sleep deprivation among individuals with chronic neck pain. Method: The cross-sectional study was conducted at the Institute of Physical Medicine and Rehabilitation, Dow University of Health Sciences (DUHS), Ojha campus, Karachi, August 10 to November 26, 2021, and comprised diagnosed patients of either gender with chronic neck pain. After recording the demographics, validated Urdu versions of the Pittsburgh Sleep Quality Index, Neck Disability Index, and Numerical Pain Rating Scale were used to assess sleep deprivation, functional disability and pain intensity, respectively. Data was analysed using SPSS 21. Result: Of the 71 patients, 45(63.4%) were females and 26(36.6%) were males with overall mean age 22.11±4.63 years. There was a strong positive correlation of Pittsburgh Sleep Quality Index with Numerical Pain Rating Scale and Neck Disability Index (p<0.05). Conclusion: Sleep deprivation was associated with neck disability in individuals with chronic neck pain. Key Words: Insomnia, neck pain, cervicalgia, sleep deprivation, prevalence.